PENGARUH KINERJA ENVIRONMENTAL, SOCIAL, GOVERNANCE DAN ESG CONTROVERSIES TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan yang Konsisten Terdaftar di Indeks Kompas100 Tahun 2020-2024) - Ruth Celine Febianti; Agus Purwanto (Diponegoro Journal of Accounting, 2026)
This study examines the environmental, social, governance performance and ESG controversies relationship on firm value. This study has a dependent variable, namely firm value as proxied by Tobin’s Q with independent variables  environmental performance, social performance, governance performance, and ESG controversies. Also firm size as a control variable. This study uses secondary data derived from Refinitiv and the financial statements of indeks Kompas100 companies listed on the Indonesia Stock Exchange  (IDX) in 2020-2024. The research sampling was carried out using purposive sampling method. 145 samples were obtained for 5 consecutive years. This study uses multiple linear regression analysis to test  the hypothesis. The finding from this study proves that environmental performance have a significant negative to firm value, social performance have no significant to firm value, governance performance have a significant positif to firm value, while ESG controversies have no significant to firm value.